"Openness" with and without Information Technology: a framework and a brief history. (December 2017) - Schlagwein, Daniel; Conboy, Kieran; Feller, Joseph; Leimeister, Jan; Morgan, Lorraine
Abstract Over the past two decades, openness (e.g. 'open' innovation, 'open' education and 'open' strategy) has been of increasing interest for researchers and of increasing relevance to practitioners. Openness is often deeply embedded in information technology (IT) and can be both a driver for and a result of innovative IT. To clarify the concept of "openness", we provide an overview of the scope of cross-disciplinary research on openness. Based on this overview, we develop a framework of openness, which proposes a higher-order concept of "openness" characterised by transparency, access, participation and democracy. The framework further distinguishes open resources, open processes and the effects of opening on particular domains. To provide the historical context and to appreciate the role of IT in openness, we discuss two historical examples of openness: the introduction of an open science model in academia (openness without IT) and the emergence of open source software development (openness with IT). We conclude by highlighting some concerns with and limitations of "openness".